Causas de decomiso durante la inspección sanitaria en bovinos que se faenan en el camal municipal del cantón Sigchos. - Chicaiza Cadena, Jefferson Santiago (2023)
The purpose of this research study was to determine the causes of forfeiture during the sanitary inspection of bovines that are slaughtered at the municipal slaughterhouse of the Sigchos Canton. The identification of the origin of the cattle in relation to the number of seizures during the sanitary inspection, the recognition of anatomopathological lesions of the organs, and the cost-benefit analysis of sanitary control. The slaughterhouse is in the Cotopaxi Province, Sigchos Canton at an altitude of 2169 m-s-n-m, and an average of 785 bovines are slaughtered annually. 65 animals were sampled during a month. The cattle came from the rural sector of Canton 85%, and from Saquisilí-Canchagua, 15% of the total number of bovines destined for slaughter was registered. Of a total of 11 pathological lesions, 55% were Hepatic Fasciola, followed by hepatic abscesses (18%), hepatic ecchymosis, hepatics petechiae, and hepatic jaundice (9%). In relation to the social cost-benefit analysis, economic losses estimated at $148,50 were determined, which affected the introducer/expender, the Sigchense population lacks knowledge related to zoonosis, public health, and food sovereignty. Therefore, it was recommended that the veterinarian and the GAD Municipal (Municipal Government) socialize and train introducers/exhibitors and consumers of the locality in these important aspects.